Evaluation of Implementation E-Government with Delone and Mclean - Sorongan, Erick; Hidayati, Qory (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
This research intends to analyze and test variables that influence implementation E-government, especially in Balikpapan city. The study uses the information system success model DeLone and McLean which has six main variables that can be used to measure the success rate of information systems. Variables that support the success of e-government that support this research include system quality and information quality as exogenous variables. Furthermore, the use and user satisfaction variables are endogenous variables that also affect the net benefits variable. Based on previous research, service quality variables have not been proven to affect endogenous variables, so the researchers omit these variables. Data collection is done by distributing questionnaires to users of e-government services in Balikpapan City as many as 100 respondents. Data processing methods with Structural Equation Modeling (SEM) using the Smart PLS 3.0 approach. This research proves the R-square value of the dependent variable user satisfaction is 62%, and the net benefit variable is 59.1%, which means that the dependent variable can be explained through independent variables in this research model. Based on the findings in the study, it shows that the quality of the system has an effect on user satisfaction but has no impact on use.